MANAJEMEN SEKOLAH DALAM MEWUJUDKAN SEKOLAH SEHAT DI SMP ISLAM CENDEKIA CIANJUR (SICC) BOARDING SCHOOL - Herlina .; Rita Retnowati; Griet Helena Laihad (JURNAL MANAJEMEN PENDIDIKAN, 2020)
SCHOOL MANAGEMENT IN REALIZING HEALTHY SCHOOLS IN SMP ISLAM CENDEKIA CIANJUR (SICC) BOARDING SCHOOLThis researched aimed to have comprehensive findings based on factual datas and information about school management at SMP Islam Cendekia Cianjur (SICC) Boarding School interms in actualizing healthy school. The qualitative method was used in order to have a comprehensive description as an output about all managerial steps; planning, organizing, actuating, and evaluating the school management at SMP Islam Cendekia Cianjur (SICC) Boarding School. All data was collected by indept interview, observation and documentation, showed that: 1) Planning for healthy school at the SICC Boarding School was issued at the beginning of its establishment with the initial stage, focusing more on procurement and completeness of school medical room (UKS), 2) Organizing health schools is the authority of the principal where the implementation of this healthy school program is assisted by several personnel, the coordinator of  healthy school , UKS builder, financial staff and the members, 3) Implementing of healthy school management is carried out by healthy school coordinators and other teams in the organizational list. The concept of  healthy school at the SICC Boarding School is to develop superior programs from UKS, it is called UKS TRIAS, PHBS habituation, and the procurement of facilities and infrastructure for UKS, 4) Controlling is carried out by monitoring and evaluating directly by school principal as the chairman of the UKS organizational list. The Controlling is focused on three aspects; human resources focused on healthy school teams, the  healthy school programme, and the procurement tools of UKS. Based on the results of the study, it is concluded that school management runs well with referring to the conditions and needs of school andcan be used as a reference model for other boarding school as well.